1996
DOI: 10.1177/004728759603500208
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Research Study on Japanese Sport Tourism in Sport-for-All Events: Case Studies of a Single-Night Event and a Multiple-Night Event

Abstract: Two empirical research studies were conducted on sport-for-all events to explore sport tourism in Japan. On the basis of survey results, Japanese sport tourists in sport-for-all events were found to be somewhat different from general tourists regarding expenditure patterns, but they showed the potential to become active tourists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(57 citation statements)
references
References 8 publications
4
44
0
6
Order By: Relevance
“…Furthermore, this specific sport tourism activity may be used, if not for mitigating tourist seasonality [50], at least as a vehicle to expand the high season to the first week of September. In line with others studies [41,42], however, this research seems to confirm the conclusions of Nogawa, Yamaguchi, and Hagi [43], highlighting how the direct economic impacts from the event are polarised into two specific fields: accommodations and food. As the data show, the athletes did not invest their money in fields not strictly connected with the competition (i.e., culture and hike with guide).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, this specific sport tourism activity may be used, if not for mitigating tourist seasonality [50], at least as a vehicle to expand the high season to the first week of September. In line with others studies [41,42], however, this research seems to confirm the conclusions of Nogawa, Yamaguchi, and Hagi [43], highlighting how the direct economic impacts from the event are polarised into two specific fields: accommodations and food. As the data show, the athletes did not invest their money in fields not strictly connected with the competition (i.e., culture and hike with guide).…”
Section: Discussionsupporting
confidence: 91%
“…On the other side, "entertainment" ranked lowest in each case, except for one (the youth softball tournament). In their discussion, the authors show how their study supports previous research carried out by Nogawa, Yamaguchi, and Hagi [43], who concluded that sport tourists spend little on activities outside the sport event.…”
Section: Conceptual Frameworksupporting
confidence: 77%
“…Suh and McAvoy (2005) showed that business travellers to Korea spent significantly more than pleasure travellers and that preference for a specific activity did not directly correlate with expenditures on the activity. In contrast, a study by Nogawa et al (1996) found that participants in Japanese sporting events differed from traditional tourists, showing that visitor expenditures were related to trip activity.…”
mentioning
confidence: 85%
“…Participación activa o pasiva en eventos deportivos Nogawa, Yamaguchi y Hagi (1996) Turista deportivo: Un visitante temporal que permanece al menos 24 horas en la zona del evento y cuyo principal objetivo es participar en un evento deportivo siendo el destino una atracción secundaria.…”
Section: Conceptualización Restrictivaunclassified